2022
DOI: 10.3389/fpls.2021.773553
|View full text |Cite
|
Sign up to set email alerts
|

De novo Transcriptome Assembly of Senna occidentalis Sheds Light on the Anthraquinone Biosynthesis Pathway

Abstract: Senna occidentalis is an annual leguminous herb that is rich in anthraquinones, which have various pharmacological activities. However, little is known about the genetics of S. occidentalis, particularly its anthraquinone biosynthesis pathway. To broaden our understanding of the key genes and regulatory mechanisms involved in the anthraquinone biosynthesis pathway, we used short RNA sequencing (RNA-Seq) and long-read isoform sequencing (Iso-Seq) to perform a spatial and temporal transcriptomic analysis of S. o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…The first is the polyketide pathway, which is observed in Photorhabdus luminescens , a gammaproteobacterium of the family Morganellaceae. It is a lethal pathogen of insects and higher plants, including Senna tora (Brachmann et al, 2007; Kang et al, 2022). In this pathway, octaketide is dehydrated, and several anthraquinone derivatives, including Endocrocin, Physcion, Rhein, and Chryso-obtusin, are synthesized (Kang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first is the polyketide pathway, which is observed in Photorhabdus luminescens , a gammaproteobacterium of the family Morganellaceae. It is a lethal pathogen of insects and higher plants, including Senna tora (Brachmann et al, 2007; Kang et al, 2022). In this pathway, octaketide is dehydrated, and several anthraquinone derivatives, including Endocrocin, Physcion, Rhein, and Chryso-obtusin, are synthesized (Kang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…It is a lethal pathogen of insects and higher plants, including Senna tora (Brachmann et al, 2007; Kang et al, 2022). In this pathway, octaketide is dehydrated, and several anthraquinone derivatives, including Endocrocin, Physcion, Rhein, and Chryso-obtusin, are synthesized (Kang et al, 2022). The second pathway is a combination of shikimate and mevalonate/methyl-D-erythritol 4-phosphate pathways, which is observed in Cinchona officinalis and Rheum tanguticum (Kang et al, 2020; Zhou et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…PKSs can be divided into types I, II, and III PKSs according to their structure [ 44 ]. Type III PKSs, the chalcone synthase superfamily, are mainly distributed in the plants, but have also been identified recently in bacteria and fungi [ 19 , 44 , 45 ]. At present, the mechanisms underlying most polyketide biosynthetic pathways are still elusive, but PKS III of plants certainly plays a key role in the initial reaction of these pathways [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies have confirmed the differences in the accumulation of secondary metabolites in different tissues of R. officinale and used RNA-seq to identify candidate genes involved in the biosynthesis of anthraquinones, etc. [ 16 , 19 , 20 , 21 , 22 ], the differences in the expression of the enzyme genes associated with the synthesis of these components are still indefinite in R. officinale .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have compared software for estimating transcript abundances in long read sequencing data (Dong et al 2023;Pardo-Palacios et al 2023b) but few reports have detailed the effectiveness of tools for RNA isoform discovery and qualification using long reads. Transcriptome assembly is an economical method for characterizing gene expression of model (Yang et al 2021;Kuo et al 2020) or non-model organisms (Kang et al 2021;Zagorščak and Petek 2021;Matra et al 2023) and for identifying novel RNAs in diseases such as cancer (Fang et al 2021;Verma et al 2015).…”
Section: Introductionmentioning
confidence: 99%